Effects of macro- and micronutrients on exercise-induced hepcidin response in highly trained endurance athletes - Dahlquist, D. T.; Stellingwerff, T.; Dieter, B. P.; McKenzie, D. C.; Koehle, M. S. (Applied Physiology, Nutrition, and Metabolism, 2017)
Iron deficiency has ergolytic effects on athletic performance. Exercise-induced inflammation impedes iron absorption in the digestive tract by upregulating the expression of the iron regulatory protein, hepcidin. Limited research indicates the potential of specific macro- and micronutrients on blunting exercise-induced hepcidin. Therefore, we investigated the effects of postexercise supplementation with protein and carbohydrate (CHO) and vitamins D3 and K2 on the postexercise hepcidin response. Ten highly trained male cyclists (age: 26.9 ± 6.4 years; maximal oxygen uptake: 67.4 ± 4.4 mL/kg·min completed 4 cycling sessions in a randomized, placebo-controlled, single-blinded, triple-crossover study. Experimental days consisted of an 8-min warm-up at 50% power output at maximal oxygen uptake, followed by 8 × 3-min intervals at 85% power output at maximal oxygen uptake with 1.5 min at 60% power output at maximal oxygen uptake between each interval. Blood samples were collected pre- and postexercise, and at 3 h postexercise. Three different drinks consisting of CHO (75 g) and protein (25 g) with (VPRO) or without (PRO) vitamins D3 (5000 IU) and K2 (1000 µg), or a zero-calorie control drink (PLA) were consumed immediately after the postexercise blood sample. Results showed that the postexercise drinks had no significant (p = 0.05) effect on any biomarker measured. There was a significant (p < 0.05) increase in hepcidin and interleukin-6 following intense cycling intervals in the participants. Hepcidin increased significantly (p < 0.05) from baseline (nmol/L: 9.94 ± 8.93, 14.18 ± 14.90, 10.44 ± 14.62) to 3 h postexercise (nmol/L: 22.27 ± 13.41, 25.44 ± 11.91, 22.57 ± 15.57) in VPRO, PRO, and PLA, respectively. Contrary to our hypothesis, the drink compositions used did not blunt the postexercise hepcidin response in highly trained athletes.